2013
DOI: 10.1080/03004430.2013.818991
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Early Childhood Environment Rating Scale, Revised Edition, ECERS-R in Arabic

Abstract: The aim of this study was to test reliabilities and validations for the Arabic translation of the Early Childhood Environment Rating Scale, Revised (ECERS-R) scale [Harms, T., Clifford, R. M., & Cryer, D. (1998). Early childhood environment rating scale, revised edition. New York: Teachers College Press]. ECERS-R mean scores were tested for reliability at the indicator, item and total score levels. Test-retest, inter-rater and internal consistency correlation agreements were used on a sample of 50 childcare ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The data obtained by both methods within this study are consistent with the Mashburn’s and colleagues results on a sample of 671 kindergarten groups from 11 USA states ( Mashburn et al, 2008 ). Rather low ECERS-R total scores were also obtained in many countries (for example, in Netherlands ( De Kruif et al, 2009 ), Bahrein ( Hadeed, 2013 ), Brazil ( Mariano et al, 2018 ), Columbia ( Betancur et al, 2021 ) etc. ), that lead researchers to propose changes in the stop-coding system of ECERS-R indicators assessment that we support ( Fujimoto et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained by both methods within this study are consistent with the Mashburn’s and colleagues results on a sample of 671 kindergarten groups from 11 USA states ( Mashburn et al, 2008 ). Rather low ECERS-R total scores were also obtained in many countries (for example, in Netherlands ( De Kruif et al, 2009 ), Bahrein ( Hadeed, 2013 ), Brazil ( Mariano et al, 2018 ), Columbia ( Betancur et al, 2021 ) etc. ), that lead researchers to propose changes in the stop-coding system of ECERS-R indicators assessment that we support ( Fujimoto et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The final score of the scale is given by the average of the raw scores of the seven subscales, the quality interpretation of which is 1-inadequate, 3-minimal (basic), 5-good, and 7-excellent [ 72 , 73 ]. Studies have shown that the ECERS has good reliability [ 74 , 75 ]. The instrument has been translated into Portuguese and is widely used in studies with Brazilian preschoolers [ 73 , 75 ].…”
Section: Methodsmentioning
confidence: 99%